The role of technology in the oil market - Cuzzi, Daniel Halloran Giuseppe (2020)
Since the first oil extraction, we can see in data a downward trend with high fluctuations in real oil prices. This pattern is reasonable once we know that the extraction process today is far more productive then it was in the nineteenth century. These productivity innovations shift the long-run supply curve for oil, with permanent effects. The fluctuations follow the business cycles which affect the oil price temporarily. Using long-run restrictions relative to productivity effect we identify a structural vector error correction model for oil price, US oil production and US industrial production, a system in which the cointegration rank is one.\\ The evidence shows that demand-side factors are the most important sources to explain unpredictable movements in oil prices and production in the short-run. The supply-side factor, productivity gains due to technological progress, is the most important source to explain unpredictable movements of the oil prices and production in the long-run. This work contributes to a better understanding of the oil market dynamics, focusing on disentangling the short-run and long-run properties.